THE PORTRAIT OF THE UPPER CLASS SOCIETY IN JANE AUSTEN’S PRIDE AND PREJUDICE - Feibriany Fabiola Valenchia Mewoh; Olga A. Rorintulus; Merlin M. Maukar (Program Studi Pendidikan Bahasa Inggris, 2023)
This study aims is to reveal the portrait of the upperclass society in Jane Austen’s Pride and Prejudice. This study classifies as qualitative descriptive because the data collected in the form of words as well as quotation from the sources. Research finding shows that the upper class life style concist of having great wealth, having party, and showing their property. Their life style proved that in Jane Austen’s novel the description of upper class life style are existed and described clearly